Success of millet cultivation in eastern Himalayas - Supriya; Singh, Magan; Kumar, Rakesh; Verma, Parkash; Kumar, Birendra (Indian Farming, 2023)
Agro-climatic region of fifth zone of the Himalaya consists of temperate to cold and frigid climate, humid to semi-humid, which obtains >2800 mm annual rainfall. Arunachal Pradesh lies in this zone where farming system is characterized by the cultivation of subsistence crops including millets. Millets such as foxtail millet, proso millet, finger millet, and pearl millet are the most frequently grown crops among millets under shifting cultivation. They provide a variety of seasonal native foods for traditional uses including ceremonies, occasions, and festivities. Practices like integrated paddy, fish and finger millet farming followed by Apatani farmers are ecofriendly and sustainable.